Implementation of Laserpuncture, Microdiet, and Synbiotic in Fish Farming Community in Boyolali Regency - Hariati, Anik Martinah; Mahariawan, I Made Dedi; Rahardjo, Seto Sugianto Prabowo; Hariyadi, Hariyadi; Suciati, Lusia Dyah; Nugroho, Nurul; Putri, Ajeng Ayu Restuaning; Permatasari, Felyta Dian; Salsabila, Sivana Yesica Ayu; Satria, Ibnu Darma; Denanta, I Made Kresna; Dailami, Muhammad (Journal of Innovation and Applied Technology, 2025)
The community service program in Boyolali Regency aims to increase the productivity of the fisheries sector through assistance with laserpuncture technology, the application of microdiet and natural feed, and the production of synbiotics. The methods used include counseling and direct practice involving more than 40 local fish farmers. The results of the program show that the application of laserpuncture and nutritional engineering through microdiet and synbiotics tecknology are increase fish growth. Participation and positive responses from the community show high enthusiasm for new technology which has a direct impact on productivity and the local economy. It is hoped that this program can be implemented independently in sustainable fisheries businesses.